Faktor-faktor Penyebab Keraguan Karir (Career Indecision) Siswa SMA/SMK - Saputra, Edy Cahya (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
The purpose of this study is to identify the causes of career indecision among high school and vocational school students. The research method employed in this study is quantitative. The primary instrument used in this research is the Career Decision Making Difficulties Questionnaire (CDDQ). The sample in this study was 274 grade XII students in Kulon Progo Regency. Data collection was carried out in the 2024/2025 school year. The analysis carried out in this study used descriptive analysis. The results of the study based on the analysis of CDDQ questionnaire items showed that the most dominant factor causing career indecision was dysfunctional beliefs. The results of this study can be used as a basis for BK teachers or counselors to develop guidance and counseling programs so that students' career indecision can be resolved appropriately.